Maternal employment and atopic dermatitis in children: a prospective cohort study. (25th March 2013) - Wang, I.J.; Wen, H.J.; Chiang, T.L.; Lin, S.J.; Chen, P.C.; Guo, Y.L.
Summary Background Considering the early onset of atopic dermatitis (AD), which most often arises in the first year of life, risk factors occurring very early in life must be considered. Little is known about the effects of maternal occupational exposure on the development of atopic disorders in children. Objectives The aim of this study was to evaluate associations between maternal employment and childhood AD. Methods We used multistage stratified systematic sampling to recruit 24 200 mother–newborn pairs from the Taiwan national birth register. Information on maternal occupation categories, work stress, working time, shift work and potential confounders during pregnancy was gathered by questionnaires after birth. At 3 years of age, information on the development of AD was assessed by home interviews. Multiple logistic regression analysis was performed to estimate the association of maternal employment and AD. Results Overall, 11 962 out of 19 381 mothers (61·7%) worked during pregnancy. The children of mothers who worked during pregnancy had an increased risk of AD compared with those whose mothers did not work [odds ratio (OR) 1·38, 95% confidence interval (CI) 1·25–1·53]. The children of mothers with a professional or technical occupation had a higher risk of AD (OR 1·64, 95% CI 1·44–1·87). The risk of AD was found to increase with maternal work stress during pregnancy in a dose–response manner (Ptrend < 0·01). The mothers of children with AD had a longer working time than those without AD (P < 0·0001). However, no significant association between AD and maternal shift work was found. Conclusions Working in professional or technical occupations increased the risk of childhood AD in addition to work stress during pregnancy.